Sistem Penerimaan Siswa Baru Berbasis Web Pada SMA Negeri 1 Pulokulon - Anam Azwar Hamidi, 10.01.55.0145 (Information Technology and Telematics, 2017)
Abstract: The event admission of new students has been done manually so that less effective and efficient . For it takes a new admissions system based web effective and efficient , and can be accessed anytime and anywhere by prospective new students . This research uses the waterfall  as a systems development method , where in the method includes needs analysis , system design , implementation , testing and maintenance . From it  was produced a new admissions system which more effective , efficient , accessible anytime and anywhere , and to facilitate the committee in the reporting process . Keywords : admission of new students,  web, waterfall